The Resilience and Stress on Bacterial Vaginosis among Reproductive Age Women in the Coastal area of Ampenan, Kota Mataram - Ika Nur Pratiwi; Elsi Dwi Hapsari; Nuring Pangastuti (Jurnal Ners, 2014)
Introduction: Bacterial Vaginosis (BV) is a common vaginal condition produced by overgrowth of anaerobic bacteria. Stress can alter women’s reproductive health in many ways; one of them is increasing the risk for bacterial vaginosis. In facing stressful life conditions, resilience plays an important role to maintain optimal function and prevent traumatic experience.Methods: This research was an analytical observational study with cross sectional design. Questionnaires were given to 104 women in reproductive age between November 2013 and January 2014. Resilience and stress were assessed using The Connor-Davidson Resilience Scale (CD-RISC) and Self Reporting Questionnaire respectively, and bacterial vaginosis status was diagnosed using Amsel’s criteria. Statistical analysis was performed using chi square test and multiple logistic regressions.Results: Bivariate analysis showed significant relations between resilience (p=0,005), stress (p=0,002), frequency of sexual intercourse within 1 week (p= 0,015) and the bacterial vaginosis incidence. Multivariate analysis showed stress was the most influential factor OR=3,9 (95% CI=1,478–10,562).Discussion: Resilience and stress were significantly with increased risk of having bacterial vaginosis.